Pokročilé metody studia vzájemných interakcí proteinů s DNA - Béresová, Lucie; Lenobel, René (Chemické listy, 2017)
DNA-protein interactions play an essential role in many regulatory mechanisms such as replication, transcription or translation and are responsible for the maintenance of the genome integrity. Isolation, identification and subsequent characterization of the biological function of DNA binding proteins propose insight into the pathological mechanisms that underlie various diseases. This review brings an overview of methods used for isolation and identification of DNA binding proteins (DNA-affinity chromatography coupled with quantitative proteomics and mass spectrometry) and subsequent methods for the characterization of their biological functions (fluorescence microscopy). Principles, advantages and disadvantages of individual methods are briefly discussed.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; DNA vazebné proteiny; retardační test; vazba proteinů; Chromatography, Affinity; DNA; Microscopy, Fluorescence; Electrophoretic Mobility Shift Assay; Protein Binding; chromatografie afinitní; fluorescenční mikroskopie; DNA-Binding Proteins